PENDEKATAN DESIGN THINKING DALAM STRATEGIC DESIGN ENTREPRENEURSHIP UNTUK PENGEMBANGAN CREATIVE MARKETING AGENCY: STUDI KASUS KAMAR ATAS - Rahmadani, Indri Kristanty; Soegoto, Eddy Soeryanto; Wahdiniwaty, Rahma; Bachtiar, Adam Mukharil; Sumitra, Irfan Dwiguna (Universitas Komputer Indonesia, 2025)
The development of the creative industry has encouraged the emergence of various creative marketing agencies that rely on creativity and design strategies as competitive advantages in entrepreneurial activities. Design is not merely positioned as a visual element, but also as a strategic approach that shapes business value, strengthens brand identity, and enhances corporate competitiveness. This study aims to analyze design-based entrepreneurship strategies in the business development of a creative marketing agency through a case study of KAMAR ATAS. The research employs a qualitative approach using a case study method, with secondary data derived from company profiles, business documentation, and relevant literature. The findings indicate that the implementation of design as an entrepreneurship strategy at KAMAR ATAS is manifested through the integration of creative services, the utilization of integrated media, and the strengthening of brand identity across various marketing activities. These strategies contribute to increasing business value and ensuring business sustainability amid competition in the creative industry. This study is expected to provide a conceptual contribution to the discourse on design-based entrepreneurship, particularly in the development of creative marketing agencies. Key Words: Entrepreneurship, Strategic Design, Creative Industry, Creative Marketing Agency